THE IMPACT OF THE RESULTS ACHIEVED ON WHEAT CULTIVATION AND THE IMPORTANCE OF EFFECTIVE IRRIGATION SYSTEM ON THE GROSS DOMESTIC PRODUCT PER CAPITA - Nela-Loredana CĂRĂBA-MEIȚĂ; Florin DINCĂ (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
Romanian agriculture enjoys one of the highest land allocations, with at the level of 2013 the land fund of Romania being made up of about 14.61 million ha of agricultural land (61,30% of the country's surface), each resident returning an area of 0.68 ha of agricultural land and 0,43 ha of arable land. Most of the existing arable land is grown mainly with so-called large crops, namely wheat and maize. In order to emphasize the importance of one of the two crops mentioned, wheat, and of the technological tools used to achieve it on Romania's economy, an analysis of the impact it has on the GDP per capita is carried out. For this purpose, the correlation between the variables considered in an econometric model was determined as follows: Gross domestic product per capita - dependency variable, gross value of wheat production, average wheat yield per hectare and agricultural area actually irrigated. The results obtained show that there is a strong link between the results of agricultural land work and the macroeconomic indicator of gross domestic product per capita.